Regarding the Verb “ĮTAKOTI” - Smetona, Antanas (Lietuvių kalba, 2021)
The first attempts to correct the verb įtakoti and, naturally, its derivatives were observed in the 1970s. The main assumption for correcting (not to mention a certain “tradition” of correcting) is as follows: įtaka – an inflectional derivative from įtekėti, therefore suffixal derivatives with -oti are not possible from the systemic perspective. Thus, this is the influence of the Russian language. However, such an assumption is erroneous and originates from misinterpretation of derivation and history of correcting. The article aims to show that, on the one hand, įtaka → įtakoti can be seen as a regular model of derivation and, on the other hand, if the noun įtaka is considered to be a loan translation, there is no reason for thinking that it functions in the language differently from all the other a-stem nouns, which serve as basis for derivatives with the suffix -oti. Abundancy of systemic examples of derivative verbs with the suffix -oti shows that the neologism įtakoti are in the same group with pasakoti and sąlygoti. They are prefixal verbs, i.e., derivatives with the suffix -oti from prefixal deverbative nouns: įtekėti → įtaka → įtakoti; nuimti → nuoma → nuomoti; pasekti → pasaka → pasakoti; pravežti → pravėža → pravėžoti; sulygti → sąlyga → sąlygoti. Therefore, correction of the verb įtakoti is not justified from the perspective of systemic word derivation.If įtaka is generally regarded as a part of derivational system of the Lithuanian language (and this is true, because it is a submorphemic loan translation, europeism, book neologism, although structurally successfully matching with examples of productive derivation models and likely to be influenced by analogous processes), its functioning in the Lithuanian language does not differ from other a-stem nouns – the derivational model of suffix -oti from the a-stem is abundant. The derivatives with this suffix are frequently derived from base nouns as well as from deverbatives, sometimes even from prefixal or concrete or even abstract nouns; the meaning of derivation does not fall out of the context here. Names of persons with the suffix -tojas are formed in big numbers and a systemic way from derivatives with the suffix -oti  and with the root of verb – pasakotojas, sąlygotojas, nuomotojas, pravėžotojas, įtakotojas.The suffix -oti is successfully used to derive verbs from prefixal deverbatives, although some limitations can also be observed – the derivative with suffix -oti is not made from įlanka. This leads only to one conclusion – a theoretical approach to a model of derivation has to be all-encompassing and considering various possibilities. Moreover, exaggerated support/denial of a certain model leads to erroneous generalizations. In general, in such complex systems (a) there is always a considerable diversity of non-systemic usage – due to different frequency of usage as well as because of historical and cognitive reasons, (b) there are always blank spaces that appear due to formally different but semantically identical or very close derivation models, which usually have to be evaluated not only from the systemic point of view but also considering a common sense of language and live speech of people (aras/erelis, siuvėjas/siūtojas, rašytojas/rašėjas, pasakoti/padangoti…).Due to all the aforesaid circumstances, the verb įtakoti is a systemic derivative/loan translation, which occupies a reasonable place in one or another derivation sub-system in the Lithuanian language as well as a fact of live speech, which does not contradict the systemic structure of language.
Keywords: word-formation; derivation; submorphemic loan translation; calque